Endoscopic management of non-ampullary duodenal adenomas - Amoyel, Maxime; Belle, Arthur; Dhooge, Marion; Ali, Einas Abou; Hallit, Rachel; Prat, Frederic; Dohan, Anthony; Terris, Benoit; Chaussade, Stanislas; Coriat, Romain; Barret, Maximilien (Endoscopy International Open, 2022)
Duodenal polyps are found in 0.1 % to 0.8 % of all upper endoscopies. Duodenal adenomas account for 10 % to 20 % of these lesions. They can be sporadic or occur in the setting of a hereditary predisposition syndrome, mainly familial adenomatous polyposis. Endoscopy is the cornerstone of management of duodenal adenomas, allowing for diagnosis and treatment, primarily by endoscopic mucosal resection. The endoscopic treatment of duodenal adenomas has a high morbidity, reaching 15 % in a prospective study, consisting of bleeding and perforations, and should therefore be performed in expert centers. The local recurrence rate ranges from 9 % to 37 %, and is maximal for piecemeal resections of lesions > 20 mm. Surgical resection of the duodenum is flawed with major morbidity and considered a rescue procedure in cases of endoscopic treatment failures or severe endoscopic complications such as duodenal perforations. In this paper, we review the existing evidence on endoscopic diagnosis and treatment of non-ampullary duodenal adenomas.